Amendments of European Convention on Human Rights, Protocol No.14 - KarapanÃ§o, Albana; KarapanÃ§o, Ina (Mediterranean Journal of Social Sciences, 2012)
Human rights are defined as those rights which are fundamental to our nature and without them we cannot live as humanbeings. This article is focused on the European Convention of Human Rights as a very important international treaty. The effectivemachinery of European Convention of Human Rights, in an unique and unprecedented way has provided its data regularly to solveindividual requirements and also in the overall impact on international law and practice. The article is compiled in two parts: the center ofthe first part is the European Convention of Human Rights in chronological flow and the second part is a detailed treatment of ProtocolNo. 14. The European Convention on Human Rights has always been a dynamic act, reflecting the needs of time. Proof of suchdynamism is the large number of protocols that have entered into force and continuous improvements.The purpose of Protocol No. 14was to extend the effectiveness of the Court to act and short proceedings.